A Three-Layer Virtual Director Model for Supporting Automated Multi-site Distributed Education - Yu, Bin; Zhang, Cha, Yong Rui; Nahrstedt, Klara (2006)
In multi-site distributed education (MSDE), video streams from multiple sites are available. To best utilize the limited screen space at each site, we develop a customizable, automated display management system in this paper, i.e., only user-preferred streams will be shown as triggered by events and timers. The configuration of such user preference, however, is challenging because it has to be both human-friendly and machine-friendly. To address this challenge, we propose a three-layer virtual director model. In the user layer, we identify three categories of parameters that can represent a wide range of user preferences yet are easy to use. These preferences are then automatically translated into a machine-friendly timed automaton in the execution layer. The automaton is simulated dynamically, which selects a subset of streams to show on the screen through a display layer. Evaluation results demonstrate the correctness and efficiency of the proposed framework.